2015
DOI: 10.1136/bjsports-2015-094704
|View full text |Cite
|
Sign up to set email alerts
|

Early mobilisation versus plaster immobilisation of simple elbow dislocations: results of the FuncSiE multicentre randomised clinical trial

Abstract: NTR 2025.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 26 publications
3
59
0
2
Order By: Relevance
“…The FuncSiE trial compared clinical outcome of early mobilization and plaster immobilization in patients with a simple elbow dislocation. The results of this study showed that early mobilization resulted in earlier recovery of elbow function and work resumption [12].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The FuncSiE trial compared clinical outcome of early mobilization and plaster immobilization in patients with a simple elbow dislocation. The results of this study showed that early mobilization resulted in earlier recovery of elbow function and work resumption [12].…”
Section: Introductionmentioning
confidence: 62%
“…The trial is registered at the Netherlands Trial Register (NTR2025). The results of this study and the study protocol can be read elsewhere [12,13]. The study was approved by the Medical Research Ethics Committee.…”
Section: Settings and Participantsmentioning
confidence: 99%
“…After early mobilization and fixation with a cast after reduction, the time taken for returning to the job was 10 and 18 days, respectively, in the study by Iordens et al (14), but 3.2 and 6.6 days, respectively, in the study by Maripuri et al (9) In our study, patients returned to their jobs after 12 days (range, 10-16 days) on average. In the literature, the rate of repeating dislocation after simple elbow dislocations is 0.6%.…”
Section: Discussionmentioning
confidence: 64%
“…In a study comparing early mobilization and immobilization after reduction, it was statistically demonstrated that the joint range of motion in the 6 th week was to be better in the early mobilization group, but the results were similar at the end of the 1 st year (14). In 43 simple elbow dislocations that were retrospectively evaluated by De Haan et al (11), while a mean flexion degree of 141.0° was obtained in the long term, a mean extension loss of 5.5° was detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation